Do Phone and Internet Have Role to Promote Economic - Rika Nurlela; Taufiq c. Dawood; Aliasuddin Aliasuddin (Research Collaboration Community (RCC), 2021)
As one of the developing countries in the world, Indonesia is very active in developing ICT. The dependence of the Indonesian people on ICT increases every year. The two ICT indicators experiencing rapid development are the telephone and the internet. This study aims to analyze the effects of fixed-line phone users, mobile phone users, and internet users on economic growth in Indonesia. The panel data used in this study is panel data from 33 provinces in Indonesia from 2011–2019. The results showed that mobile phone users and internet users have positive effects on economic growth. However, fixed-line phones have a negative and insignificant influence on economic growth. Advances in technology have shifted fixed-line phones to smartphones. The government is expected to control and direct mobile phones and the internet for productive activities to encourage economic improvement.